CLINICOEPIDEMIOLOGICAL AND ETIOLOGICAL PROFILE OF CHRONIC DIARRHEA IN CHILDREN 1 TO 18 YEARS OF AGE: A HOSPITAL BASED CROSSECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Chronic diarrhea lasts for more than 14 days, is noninfectious and associated with malabsorptive features like abdominal distention, failure to gain weight with fall in growth chart percentiles. The approach and management of chronic diarrhea is different from the management of acute diarrhea. Chronic diarrhea can have many myriad etiologies. Although etiologies are more or less same, their relative frequency can differ according to the regions it is reported from. We therefore tried to look at clinical features and possible etiologies of chronic diarrhea among children presenting to a tertiary care hospital. Being a referral hospital there is a subtle cjhance of referral bias. Celiac disease turned out to be the most common cause of chronic diarrhea followed by cow’s milk protein allergy. Secondary lactose intolerance was less common. Toddlers diarrhea was also less probably due to referral bias. Pallor and anemia was the most common presenting clinical sign apart from diarrhea.